Matematika Dan Fungsinya Dalam Pengembangan Lembaga Pendidikan Islam - Nurhilaliyah (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
This study aims to analyze the role and function of mathematics in the development of Islamic educational institutions, with a focus on the context of Indonesia and Southeast Asia. The method used is a literature review by examining various sources such as scientific journals, academic books, policy documents, and data from the Ministry of Religious Affairs of the Republic of Indonesia. The results show that mathematics has multidimensional functions in the development of Islamic educational institutions, including: a historical role as an integral part of the classical Islamic scholarly tradition inherited from Al-Khwarizmi, Omar Khayyam, and Ibn al-Haytham; a curricular function in shaping the cognitive competencies of students; a managerial function in financial management, strategic planning, and institutional quality assurance; an integrative function that connects Islamic values with the teaching of science; and a contributive function toward producing competitive graduates. The study found that among the 42,433 pesantren (Islamic boarding schools) and 87,605 madrasahs in Indonesia, integrating mathematics with Islamic values is an effective strategy to increase learning motivation by up to 10% and learning outcomes by up to 23%. In conclusion, mathematics is not merely a general subject but a strategic instrument for realizing a holistic, competitive, and character-based Islamic education vision. Recommendations are provided for developing an integrated curriculum, improving teacher competencies, and strengthening digital infrastructure in Islamic educational institutions.